The Poisoned Pilgrim : a Hangman's Daughter tale - Pötzsch, Oliver (Pötzsch, Oliver. Hangman's daughter tale., 2013)
In 1666, Magdalena, the hangman's daughter and her physician husband arrive at Andechs Abbey where they, along with Jakob Kuisl, the hangman of Schongau, set out to find the mysterious Brother Virgilius, a monk, watchmaker and inventor, who disappeared after creating an eerie automata.